2021
DOI: 10.3390/s21113679
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Jumping for Legged Robot Based on Quadratic Programming

Abstract: The highly dynamic legged jumping motion is a challenging research topic because of the lack of established control schemes that handle over-constrained control objectives well in the stance phase, which are coupled and affect each other, and control robot’s posture in the flight phase, in which the robot is underactuated owing to the foot leaving the ground. This paper introduces an approach of realizing the cyclic vertical jumping motion of a planar simplified legged robot that formulates the jump problem wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The researchers provided the computer simulation to study the forces [3][4][5] that hold water striders on the surface of the water. They concluded that to allow the designed object to move and jump on the surface of the water without the risk of drowning, they need to apply superhydrophobic material or material whose surface is not wetted by water [6].…”
Section: Specificity Of Water Strider-like Robotmentioning
confidence: 99%
“…The researchers provided the computer simulation to study the forces [3][4][5] that hold water striders on the surface of the water. They concluded that to allow the designed object to move and jump on the surface of the water without the risk of drowning, they need to apply superhydrophobic material or material whose surface is not wetted by water [6].…”
Section: Specificity Of Water Strider-like Robotmentioning
confidence: 99%
“…The innovation of the controller is as follows: Different from ref. [12–17], the controller takes into account the influence of arm swing on the jumping motion. Linear momentum and angular momentum are coordinated and optimized in the controller to control the speed of COM. The controller adjusts the posture of the robot during the flight phase to prepare for a smooth landing. …”
Section: Introductionmentioning
confidence: 99%
“…Different from ref. [12–17], the controller takes into account the influence of arm swing on the jumping motion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations